Reliability of genetic bottleneck tests for detecting recent population declines - PEERY, M. ZACHARIAH; KIRBY, REBECCA; REID, BRENDAN N.; STOELTING, RICKA; DOUCET-BËER, ELENA; ROBINSON, STACIE; VÁSQUEZ-CARRILLO, CATALINA; PAULI, JONATHAN N.; PALSBØLL, PER J. (Molecular ecology, 2012)
The identification of population bottlenecks is critical in conservation because populations that have experienced significant reductions in abundance are subject to a variety of genetic and demographic processes that can hasten extinction. Genetic bottleneck tests constitute an appealing and popular approach for determining if a population decline has occurred because they only require sampling at a single point in time, yet reflect demographic history over multiple generations. However, a review of the published literature indicates that, as typically applied, microsatellite‐based bottleneck tests often do not detect bottlenecks in vertebrate populations known to have experienced declines. This observation was supported by simulations that revealed that bottleneck tests can have limited statistical power to detect bottlenecks largely as a result of limited sample sizes typically used in published studies. Moreover, commonly assumed values for mutation model parameters do not appear to encompass variation in microsatellite evolution observed in vertebrates and, on average, the proportion of multi‐step mutations is underestimated by a factor of approximately two. As a result, bottleneck tests can have a higher probability of ‘detecting’ bottlenecks in stable populations than expected based on the nominal significance level. We provide recommendations that could add rigor to inferences drawn from future bottleneck tests and highlight new directions for the characterization of demographic history.